2018
DOI: 10.1055/s-0038-1675332
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Academic Rank and NIH Funding among Academic Maternal–Fetal Medicine Physicians in the United States

Abstract: Objective This article evaluates gender differences in academic rank and National Institutes of Health (NIH) funding among academic maternal–fetal medicine (MFM) physicians. Study Design This was a cross-sectional study of board-certified academic MFM physicians. Physicians were identified in July 2017 from the MFM fellowship Web sites. Academic rank and receipt of any NIH funding were compared by gender. Data on potential confounders were collected, including years since board certification, regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 21 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Seven studies adjusted for potential confounders, including years in practice (Dossani et al , 17 Gawad et al , 18 Jena et al , 16 Orhurhu et al , 53 Riaz et al , 54 Smith et al 55 and Sperling et al 56 ); specialty (Jena et al ); publications (Dossani et al , Gawad et al , Jena et al , Riaz et al and Sperling et al ); h-index (Dossani et al , Gawad et al , Orhurhu et al , Riaz et al and Sperling et al ); additional PhD (Dossani et al , Gawad et al and Sperling et al ); and institution (Dossani et al , Jena et al , Orhurhu et al , Riaz et al and Sperling et al ). Pooling the adjusted effect estimates comparing 64 469 men to 32 063 women demonstrated that men were 1.83 times more likely to be full professors (adjusted OR 1.83, 95% CI 1.04 to 3.20, p=0.03, I 2 =91%; figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies adjusted for potential confounders, including years in practice (Dossani et al , 17 Gawad et al , 18 Jena et al , 16 Orhurhu et al , 53 Riaz et al , 54 Smith et al 55 and Sperling et al 56 ); specialty (Jena et al ); publications (Dossani et al , Gawad et al , Jena et al , Riaz et al and Sperling et al ); h-index (Dossani et al , Gawad et al , Orhurhu et al , Riaz et al and Sperling et al ); additional PhD (Dossani et al , Gawad et al and Sperling et al ); and institution (Dossani et al , Jena et al , Orhurhu et al , Riaz et al and Sperling et al ). Pooling the adjusted effect estimates comparing 64 469 men to 32 063 women demonstrated that men were 1.83 times more likely to be full professors (adjusted OR 1.83, 95% CI 1.04 to 3.20, p=0.03, I 2 =91%; figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study demonstrated no difference in the proportion of men versus women receiving federal research funding after controlling for time in practice, additional degrees, publications and h-index (adjusted OR 1.23, 95% CI 0.79 to 1.92). 56 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Academic physician literature shows that female academic physicians face many of the same barriers as PA educators regarding salary and promotion parity, including balanced work and home responsibilities, 28,29 lack of mentorship, 30 and research. 31 However, the qualitative data in this study show there are 2 themes that are unique to PA educators: a lack of standardization of a doctoral degree within the PA profession 32 and variability in career tracks at different institutions. These differences create ambiguity within the profession itself and create challenges for female PA faculty members when discussing these issues with colleagues.…”
Section: Discussionmentioning
confidence: 72%
“…Despite advancements in the past three decades, including increasing numbers of women admitted to medical schools, 1 and rising rates of female OB/GYN providers, 2 women experience gender bias in residency evaluations in OB/GYN, 3 and female Maternal-Fetal Medicine (MFM) providers have been found to experience bias in receiving academic promotions, including departmental leadership positions. 4 5 We acknowledge that literature and applications to training programs are woefully slow to change to adapt to the use of gender-inclusive language; therefore, our language and references to gender in this article conform to a binary system for gender description, despite our understanding that there are many other expressions of gender.…”
mentioning
confidence: 99%